2020
DOI: 10.3892/or.2020.7603
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin‑2 suppresses cervical cancer cell migration through AKT/mTOR‑mediated autophagy induction

Abstract: Kindlin-2 plays a carcinogenic or tumor-suppressor role in various tumors. However, its role in cervical cancer remains unclear. In the present study, kindlin-2 expression was first analyzed using public expression data and clinical specimens. It was revealed that kindlin-2 was downregulated in cervical cancer tissues, and low expression of kindlin-2 was associated with poor disease-free survival. In addition, kindlin-2 was overexpressed and knocked down in two cell lines to study its effect in cervical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Various studies have shown that autophagy is enhanced in numerous types of tumors, such as breast cancer, small cell lung cancer, and ovarian cancer [9][10][11]. However, autophagy can be cytotoxic to cancerous cells, driving them to programmed cell death [12,13]. Recently, a phase II clinical trial was conducted, using pantoprazole (an autophagy inhibitor targeting the proton pump) combined with docetaxel in the treatment of metastatic castration-resistant PCa; however, most cases were observed with limited clinical response [14].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that autophagy is enhanced in numerous types of tumors, such as breast cancer, small cell lung cancer, and ovarian cancer [9][10][11]. However, autophagy can be cytotoxic to cancerous cells, driving them to programmed cell death [12,13]. Recently, a phase II clinical trial was conducted, using pantoprazole (an autophagy inhibitor targeting the proton pump) combined with docetaxel in the treatment of metastatic castration-resistant PCa; however, most cases were observed with limited clinical response [14].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al showed that MAP7 promoted migration and invasion and progression of human cervical cancer through modulating the autophagy (Zhang et al, 2020 ). Wu et al found that kindlin 2 suppressed cervical cancer cell migration through AKT/mTOR-mediated autophagy induction (Wu et al, 2020 ). Wang et al showed that angelicin inhibited the malignant behavior of human cervical cancer potentially via inhibiting autophagy (Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that autophagy is involved in multiple signaling pathways and affects the occurrence and development of cervical cancer [24][25][26][27][28]. Studies have shown that inhibitors of the autophagy gene ATG4 can inhibit autophagy, enhance the cytotoxicity of chemotherapy drugs, and achieve the purpose of killing tumor cells [29].…”
Section: Discussionmentioning
confidence: 99%